Warming-up and evaporation characteristics of homogeneous and heterogeneous water droplets. (August 2019) - Antonov, D.V.; Kuznetsov, G.V.; Piskunov, M.V.; Vysokomornaya, O.V.; Yan, Wei-Mon
Graphical abstract: Highlights: Temperature gradient in heterogeneous drop is drastically higher than in homogeneous one. A solid particle slows down warming-up of the surrounding water. Evaporation rate of water in heterogeneous drop is higher than that of homogeneous one. Convection strongly influences warming-up of heterogeneous drop. Heat transfer at surface of heterogeneous drop is stronger than that of homogeneous one. Abstract: The study reports the experimental results of warming-up and evaporation of homogeneous and heterogeneous water droplets at high temperatures, 100–600 °C. The heterogeneous water droplet is formed by covering a solid opaque graphite particle by a thin water layer. Differences between the warming-up mechanisms of the homogeneous and heterogeneous water droplets with an initial liquid volume from 10 μl to 20 μl at the convective heating are shown. The contactless method Planar Laser-Induced Fluorescence allows the analysis of the temperature distributions inside the homogeneous droplets and inside a liquid phase of the heterogeneous droplets, laying emphasis on the novelty of the research. A maximum temperature in the central part of the liquid phase of the heterogeneous droplets is approx. 90 °C; a maximum temperature in the homogeneous droplets is approx. 50 °C. The heterogeneous droplet heats up by 20 ± 3% longer than the homogeneous one. Moreover, a warming-up rate of the liquid phase of the heterogeneous droplet is less than that of the homogeneous water droplet by 85%. However, the size decreasing rate of the heterogeneous droplets is sometimes higher than that of the homogeneous droplets by 80%. The mean and instant evaporation rate of homogeneous and heterogeneous water droplets are compared. The study discusses an influence of convection in the liquid phase of the heterogeneous droplets on evaporation characteristics. The time of the complete water evaporation decreases by 40% due to a solid inclusion presence. A dimensionless criterion of the convective heat transfer enhancement in a water droplet containing the solid opaque inclusion is used to generalize the experimental data. The findings obtained are critically important to improve the existing high-temperature technologies and methods of water purification and to develop innovative ones.